2022
DOI: 10.3390/jpm12071103
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Difference in Tocilizumab Efficacy in the Treatment of Severe COVID-19 Caused by Different SARS-CoV-2 Variants

Abstract: Tocilizumab (TOC) is presumed to be an effective and safe treatment for severe COVID-19, but its usefulness has not been yet investigated for different SARS-CoV-2 variants. This study aimed to evaluate the influence of TOC on mortality in patients with severe COVID-19 caused by Delta and non-Delta SARS-CoV-2 variants. In a retrospective analysis, we compared the medical records of 78 and 224 patients with severe COVID-19 due to Delta and non-Delta variants, respectively. A total of 30 patients with Delta and 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
1
2
0
4
Order By: Relevance
“…Other studies [7,8,10,11,19], including platform trials [5,6], have reported a favorable effect of tocilizumab in alpha, beta or gamma cases; however, the benefit of tocilizumab in patients infected with delta, which is reported to be more virulent [20], or in patients infected with omicron, which is, in contrast, reputed to be less virulent [21], remained disputable. To the best of our knowledge, this study was the first to report the use of tocilizumab in a large cohort of severe COVID-19 patients infected with the delta and omicron VOC, suggesting that, among the patients developing a severe form of the disease, the mortality rates were similar in the omicron and delta cases, as it has been reported with previous VOCs [14]. In the same line, some authors have highlighted that the rate of severe COVID-19 may change depending on the VOC, but, in cases of severe forms, they reported that the cytokine secretion remained stable and independent from the VOC [22].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Other studies [7,8,10,11,19], including platform trials [5,6], have reported a favorable effect of tocilizumab in alpha, beta or gamma cases; however, the benefit of tocilizumab in patients infected with delta, which is reported to be more virulent [20], or in patients infected with omicron, which is, in contrast, reputed to be less virulent [21], remained disputable. To the best of our knowledge, this study was the first to report the use of tocilizumab in a large cohort of severe COVID-19 patients infected with the delta and omicron VOC, suggesting that, among the patients developing a severe form of the disease, the mortality rates were similar in the omicron and delta cases, as it has been reported with previous VOCs [14]. In the same line, some authors have highlighted that the rate of severe COVID-19 may change depending on the VOC, but, in cases of severe forms, they reported that the cytokine secretion remained stable and independent from the VOC [22].…”
Section: Discussionsupporting
confidence: 73%
“…Unfortunately, in numerous countries, several factors have limited the use of tocilizumab, such as drug shortages, high cost or late approval (December 2021 in Europe, December 2022 in the USA). Therefore, real-life data on tocilizumab treatment remain scarce, especially in patients infected with delta or omicron VOCs [13][14][15]. Moreover, its use is questionable in omicron cases.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that TCZ efficacy in severe COVID-19 does not differ between Delta or non-Delta virus variants. The Delta variant also did not increase the mortality risk when compared to other virus strains [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Вірусні інфекції теж можуть викликати постінфекційні розлади з боку ШКТ. Крім того, на частоту розладів з боку ШКТ, підшлункової залози та гепатобіліарної системи впливають препарати із потенційними побічними ефектами, такі, як антибіотики, противірусні препарати, гідроксихлорохін та біологічні препарати, які часто використовують для лікування пацієнтів, уражених COVID-19 [14].…”
unclassified
“…Враховуючи постковідні симптоми, було розроблено комплексне лабораторне дослідження, яке дозволить оцінити стан організму після перенесеного COVID-19 та визначити найбільш уражені органи та системи організму. Терапевтичні заходи, вчасно застосовані після отримання результатів аналізів, можуть дозволити зменшення проявів постковідного синдрому та покращити якість життя після COVID-19 [14].…”
unclassified